2020
DOI: 10.1186/s13195-020-00599-1
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of cholinergic neurotransmission, within a cognitive challenge paradigm, is indicative of Aβ-related cognitive impairment in preclinical Alzheimer’s disease after a 27-month delay interval

Abstract: Background: Abnormal beta-amyloid (Aβ) is associated with deleterious changes in central cholinergic tone in the very early stages of Alzheimer's disease (AD), which may be unmasked by a cholinergic antagonist (J Prev Alzheimers Dis 1:1-4, 2017). Previously, we established the scopolamine challenge test (SCT) as a "cognitive stress test" screening measure to identify individuals at risk for AD (Alzheimer's & Dementia 10(2):262-7, 2014) (Neurobiol. Aging 36 (10): 2015). Here we aim to demonstrate the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Interdisciplinary harmonization of cognitive progression markers with biomarker models such as the AT(N) framework or other disease models of dementia may aid in the detection of preclinical AD and thereby the screening for (secondary) prevention clinical trials. However, methodological changes within neuropsychology that reexamine theories of cognitive aging and creatively test alternative approaches to assessment are also needed [93,94]. For example, Snyder and colleagues recently described the rationale for administering a pharmacologic stress test (subcutaneous injection of scopolamine hydrobromide) to transiently impair cholinergic tone in atrisk cognitively normal adults [95].…”
Section: Discussionmentioning
confidence: 99%
“…Interdisciplinary harmonization of cognitive progression markers with biomarker models such as the AT(N) framework or other disease models of dementia may aid in the detection of preclinical AD and thereby the screening for (secondary) prevention clinical trials. However, methodological changes within neuropsychology that reexamine theories of cognitive aging and creatively test alternative approaches to assessment are also needed [93,94]. For example, Snyder and colleagues recently described the rationale for administering a pharmacologic stress test (subcutaneous injection of scopolamine hydrobromide) to transiently impair cholinergic tone in atrisk cognitively normal adults [95].…”
Section: Discussionmentioning
confidence: 99%
“…It was consistent with the fact that OH, -NH, C-H, -NH 2 , C-N, C=O and C-O bonds contained in GO and CS (curve a and b) showed stretching vibration at 3551, 3479, 3412, 1638, 1616, 1343 and 1085 cm −1 , respectively. 33 It can be observed that C-N peaks increased at 1638 cm −1 , C-O and -NH 2 peaks decreased at 1616 cm −1 in the FTIR spectra of GCS and AuNPs@GCS. This is attributed to a reaction between the C=O of GO and the -NH 2 of CS, and also the side illustrates the successful recombination of GCS (curve c) and AuNPs@GCS (curve d), which is consistent with the literature reports.…”
Section: Resultsmentioning
confidence: 87%
“…This is related to slowing the EEG waves in MCI and dementia patients [ 28 , 35 ]. The most likely physiological interpretation to explain this is the occurrence of significant brain cholinergic deficits as the basis for symptoms of cognitive decline [ 36 ]. Cholinergic regulates spontaneous activity at low frequencies, followed by the loss of neurotransmitters and slowing nerve oscillations.…”
Section: Discussionmentioning
confidence: 99%